Local Government Policy Model in Utilization of Rice Harvested by the Merauke Community - Julianto Jover Jotam Kalalo; Thimon Febby (Faculty of Law, Musamus University, 2022)
The harvest of farmers has not been absorbed optimally, Merauke rice is hampered in marketing, the government has the responsibility to pay attention to the needs of the community, especially farmers in the utilization of the rice harvest which is very abundant. local government policy making in the utilization of rice yields in Merauke district. This research is a normative and socio-legal legal research. This research was conducted at the Regional Secretariat of the Legal Division of Merauke Regency. The location of this research was chosen based on the approach of authority and the level of involvement of the agency. Primary data, and secondary data. The data collection used was literature study, observation and interviews. The analysis technique uses qualitative-descriptive data analysis. Characteristics and concepts of the policy model in the utilization of rice yields, is the existence of government and/or private policies to expand agricultural land. There is communication between government officials or private business entities with the utilization of the rice harvest. There are economic benefits for farmers. The land is dominated by land that is still forested and has not become agricultural land. It needs the support of human resources, water resources, infrastructure and financing. Influencing and livelihood conditions and the economy of local landowners and territories. Policy model in the utilization of rice yieldsÃ¢â‚¬Â in this study with the main and supporting theories after being elaborated from the literature study and abstracted from the themes in the field, namely by looking at the existence of government and/or private policies to expand agricultural land. There is communication between government officials or private business entities with the utilization of the rice harvest. There are economic benefits for farmers. The land is dominated by land that is still forested and has not become agricultural land